2017
DOI: 10.1186/s12955-017-0605-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcultural adaptation and psychometric validation of a Spanish-language version of the “Pelvic Girdle Questionnaire”

Abstract: BackgroundThe Pelvic Girdle Questionnaire is the only instrument designed to assess pain and disability specifically in pregnant or postpartum women with pelvic girdle pain. The objective of this study was the adaptation to the Spanish language and analysis of the psychometric properties of the Pelvic Girdle Questionnaire.MethodsThis is a descriptive cross-sectional study divided into two phases. In the first phase, a translation and adaptation process was performed according to international guidelines. Secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
(40 reference statements)
3
17
0
Order By: Relevance
“…Again, Swedish culture and context are similar to those in Norway, which may partly explain the similar results. The present study showed the same internal consistency for the total scale as the Spanish translation (0.96) [15]. The coefficients greater than 0.95 may suggest a redundancy among items [17].…”
Section: Validationsupporting
confidence: 70%
See 2 more Smart Citations
“…Again, Swedish culture and context are similar to those in Norway, which may partly explain the similar results. The present study showed the same internal consistency for the total scale as the Spanish translation (0.96) [15]. The coefficients greater than 0.95 may suggest a redundancy among items [17].…”
Section: Validationsupporting
confidence: 70%
“…This was expected since Norway and Sweden are neighboring and comparable countries when it comes to the sociocultural context for pregnant women. In order to have the same version of the questionnaire to translate from as other countries' translations [15,16], we chose to translate from the English version of the pelvic girdle questionnaire to Swedish and not from the original Norwegian version. A limitation with this choice is that the English version of the pelvic girdle questionnaire has not been validated.…”
Section: Translationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the Nepali PGQ showed moderate internal consistency, which is similar to the English, Iranian and Brazilian-Portuguese PGQ versions (174,188,189). The internal consistency was slightly higher in the Polish, French-Canadian, Spanish, Swedish and Japanese PGQ versions (224)(225)(226)(227)(228).…”
Section: Discussion Of the Main Findingsmentioning
confidence: 95%
“…by evaluating the psychometric properties of the PGQ in Spanish showed that the correlation coefficient with Cronbach's alpha was 0.961 and the ICC was 0.962. [17]…”
Section: Discussionmentioning
confidence: 99%